TANTANGAN DAN PELUANG MANAJEMEN SUMBER DAYA MANUSIA DI ERA REVOLUSI INDUSTRI 4.0 - Hermansyah; Syahrial Shaddiq; Khuzaini (PT. Saha Kreasi Indonesia, 2025)
The Industrial Revolution 4.0 has brought significant impacts on Human Resource Management (HRM), where technological advancements such as artificial intelligence (AI), automation, and the Internet of Things (IoT) have transformed how organizations manage their human resources. This article aims to analyze the strategic role of HRM in addressing challenges and leveraging opportunities that arise from these technological developments. This study employs a qualitative approach through a literature review to examine the role of HR managers and identify relevant strategies for managing human resources in the digital era. The findings indicate that HR managers must act as strategic partners who support employee skill development and well-being, while also adjusting policies to build an innovative and collaborative work environment. In conclusion, efficient human resource management plays a vital role in enhancing organizational competitiveness in an increasingly global and competitive market. The contribution of this study is to provide insights into the importance of adaptive human resources in supporting organizational goals amid rapid technological changes.